Evaluation in the Face of Digital Transition Challenges: A Reflection based on the experience of mapping policies to fight child educational poverty. - Rossero, Eleonora; Testore, Gaia (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
The digital transition is contributing to the availability of extensive information regarding public policies. However, the accessibility of such data is a necessary but not sufficient condition to activate processes of learning and enhance the effectiveness of interventions. Information overload does not necessarily translate into a real contribution to knowledge; it is essential that the information be systematized to provide a comprehensive view that enables understanding of where interventions are needed, to avoid the risk of duplicating similar actions. This paper explores the potential of the mapping tool, developed in 2024 to track measures aimed at combating child educational poverty in the regions of Piedmont, Liguria, and Aosta Valley, for: i) systematizing and analyzing the informational resources; ii) presenting and making this information accessible to policymakers and various stakeholders; iii) planning and evaluating interventions in this area of public policy.